#TITLE_ALTERNATIVE# - AGUNG PRABOWO (NIM: 20207056), FIESTIYO
Temperature measurement on Fundamental Physics Experiment can be done by variation measurement apparatus. Temperature measurement used microcontroller and ultrasonic sensor can replace or support in fundamental physics experiment. This temperature measurement applies time difference of ultrasonic wave propagation in gas chamber as medium. From known concept, ultrasonic wave velocity is influenced by medium temperature, so propagation time of wave will be influenced by temperature difference of medium. Gas temperature measurement is determined in closed chamber by calibration apparatus that use liquid thermometer. Experiment result has standard deviation by 1.55 oC.